2016
DOI: 10.1007/s00158-016-1531-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sensor placement for structural parameter identification

Abstract: The identification of model material parameters is often required when assessing existing structures, in damage analysis and structural health monitoring. A typical procedure considers a set of experimental data for a given problem and the use of a numerical or analytical model for the problem description, with the aim of finding the material characteristics which give a model response as close as possible to the experimental outcomes. Since experimental results are usually affected by errors and limited in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…According to Ostachowicz, structure health monitoring can be based on vibration-based monitoring, strain monitoring, elastic waves-based monitoring, electromechanical impedance-based monitoring, and comparative vacuum monitoring [46]. Although being in agreement with this general definition, the problem analysed in the paper is its simplified short-time version and should be distinguished from the structural health monitoring widely described in the literature [45][46][47][48]. Procedures of the parameter identification in structural health monitoring are based on the experimental-data considered and on the use of a numerical or analytical models for the problem description [47].…”
Section: Discussionmentioning
confidence: 90%
“…According to Ostachowicz, structure health monitoring can be based on vibration-based monitoring, strain monitoring, elastic waves-based monitoring, electromechanical impedance-based monitoring, and comparative vacuum monitoring [46]. Although being in agreement with this general definition, the problem analysed in the paper is its simplified short-time version and should be distinguished from the structural health monitoring widely described in the literature [45][46][47][48]. Procedures of the parameter identification in structural health monitoring are based on the experimental-data considered and on the use of a numerical or analytical models for the problem description [47].…”
Section: Discussionmentioning
confidence: 90%
“…Optimal FBG sensor network installation is in itself an important research field that seeks to minimize the number of sensors to achieve the objectives of the monitoring system. Several researchers are working on optimal sensor location for SHM (Beal et al, 2008; Chisari et al, 2016; Kammer, 1991). In the present research, the location of the sensor is obtained from a combination of FEM analysis and manufacturing constraints.…”
Section: The Uasmentioning
confidence: 99%
“…A more detailed review of OSP methods with particular emphasis on vibration measurements can be found in [12][13][14][15].…”
Section: Optimisation Algorithms For Optimal Sensor Placementmentioning
confidence: 99%